DISCRETENESS ERRORS OF FREQUENCY LEVEL GAUGES AND METHODS OF THEIR MINIMIZATION - V. B. Goncharov; V. D. Ivchenko (Российский технологический журнал)
The report examines the main causes of errors in the measurement of the level of rocket fuel components by variable frequency sensors - the speed of the wave propagation, the period of modulation, the nonlinearity of the amplitude-frequency characteristics of the generator and circuits, frequency deviation and difference frequency. The proposed options minimise bias. Methods of reducing the influence of discreteness errors in a frequency modulated (FM) transmitters (adaptive voltage control modulation, the introduction of an additional slow modulation of the carrier frequency, the spectral analysis method) are presented.